Perioperative management of aortic stenosis in patients undergoing non-cardiac surgery - Herrera, Roberto A.; Smith, Mark M.; Mauermann, William J.; Nkomo, Vuyisile T.; Luis, Sushil Allen (Frontiers in Cardiovascular Medicine, 2023)
Aortic stenosis is one of the most common cardiac valve pathologies in the world and its prevalence increases with age. Although previously associated with increased perioperative mortality, more recent studies suggest that mortality rates may be decreasing. Recent guidelines suggest that major non-cardiac surgery can be performed safely in asymptomatic severe aortic stenosis patients with close hemodynamic monitoring. Among symptomatic patients, the guidelines recommend aortic valve intervention prior to major non-cardiac surgery because of a reduction in the incidence of postoperative heart failure and improved rates of long-term overall survival. This review provides a comprehensive and contemporary review of the perioperative management of patients with severe aortic valve stenosis.